Improving Biosecurity Knowledge and Injection Techniques in Small-Scale Cattle Farming Through an International Student Summer School - Farah Diba ‘Izzati; Ari Wibowo; Suhardi (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2026)
This community service program aims to enhance the knowledge and practical skills of international students regarding livestock biosecurity and injection techniques in small-scale beef cattle farming systems. The activities were conducted through workshops, hands-on practical sessions, and group discussions as part of a structured summer school program. A questionnaire was used as an evaluation instrument to assess participants’ knowledge, perceptions, and confidence levels. The program involved 11 international students from diverse backgrounds who participated in field-based learning activities at a livestock training facility in East Kalimantan, Indonesia. The results showed that 64% of participants had prior awareness of biosecurity, and all participants (100%) recognized its importance in preventing disease outbreaks. However, only 27% reported confidence in explaining injection techniques, indicating the need for more intensive practical training. In addition, 91% of participants perceived that small-scale farmers lacked adequate knowledge of biosecurity, suggesting a substantial gap in field-level awareness. The main challenges identified were limited knowledge (45%) and financial constraints (36%). Overall, the program contributed to improving participants’ understanding and awareness while highlighting the strategic role of international students as agents of education in promoting biosecurity practices within local farming communities.